From Mexico to the Beagle Channel: A review of metal and metalloid pollution studies on wildlife species in Latin America - Di Marzio, A.; Lambertucci, S.A.; Fernandez, A.J. Garcia; Martínez-López, E. (Environmental research, 2019)
Emissions of metals and metalloids (Hg; Cd; Cr; Cu; Pb; Ni; Zn; Fe; Mn; As; Se) generated by natural (e.g., geothermal activity) or anthropic causes (eg., industry or mining) represent a worldwide contamination problem, especially in developing countries. Exposure to high concentrations of these elements is harmful to living beings, including humans. Information on this type of contamination is scarce and fragmented, limiting research which could benefit from these data. To know the state of the research, we reviewed the studies of environmental pollution by metals and metalloids carried out on animal species in Latin America. The use of animals as biomonitors of contamination by metals and metalloids is a continuously expanding practice that allows for early detection of problems. With this work, we were able to identify the most studied areas in Latin America (Amazon, Gulf of California, coastal area between Rio de Janeiro and Florianopolis and River Plate Estuary). Moreover, we provide information on the most studied metals (Hg, Cd, Cu, Pb, Zn) and wild species, which evidence the use of endangered species. The data reviewed should help researchers to direct their efforts towards sparsely researched areas and facilitate bibliographic consultation of scientific information on exposure to metals and metalloids in Latin America. •High levels of pollution have been detected in the Caribbean, Central & South America.•Studies on species consumed by humans (mainly fishes) showed metal levels exceeding safety limits.•Aquatic ecosystems are better studied; studies of terrestrial ecosystems are needed.•A common biomonitoring protocol would be advisable to develop research strategies.